G371 Defining transient abnormal myelopoiesis (TAM) and silent tam in neonates with down syndrome. (27th April 2016) - Bhatnagar, N; Nizery, L; Richmond, H; Perkins, K; Kennedy, A; Metzner, M; Alford, K; Bonnici, J; Roy, A; Anthony, M; Blumberg, R; Curley, A; et al.
Abstract : Background and aims: Children with Down syndrome (DS) have a 150-fold-increased risk of acute myeloid leukaemia (ML-DS) in the first 5y of life (peak age 12–15 months). ML-DS is preceded by Transient Abnormal Myelopoiesis (TAM), a neonatal pre-leukaemic disorder unique to DS. Recent studies of clinically-diagnosed TAM show acquired mutations in the GATA1 gene in all cases. However, the true clinical spectrum of TAM is unknown since previous retrospective reports have not systematically evaluated blood films or GATA1 mutation status. The purpose of our study was to prospectively determine the clinical, haematological, molecular features and natural history of TAM. Methods: Neonates with karyotypically-confirmed DS were prospectively enrolled to the Oxford-Imperial DS Cohort Study (OIDSCS) from October 2006. Detailed clinical and FBC/blood film data were matched to GATA1 mutational analysis by Sanger sequencing/Direct High Performance Liquid Chromatography (Ss/DHPLC). Targeted next-generation-sequencing (NGS) was used to determine clone size and/or detect small (<5%) mutant GATA1 clones. TAM was prospectively defined as: >10% peripheral blood blasts and GATA1 mutation(s) detected by Ss/DHPLC. Silent TAM was defined as: blasts <10% and GATA1 mutation (s) detected by Ss/DHPLC or NGS. Results: Of 382 neonates recruited to OIDSCS by June 2014, 39 (10.2%) had TAM. Although no clinical features were specific for TAM, hepatosplenomegaly, pericardial/pleural effusion and skin rash were more common in TAM (p < 0.0001, p < 0.01, p < 0.05) than DS neonates without GATA1 mutations. The only haematological features specific for TAM were blasts >20% and WBC >45 × 10 9 /L. Ten neonates with TAM and 8 without TAM had 11–20% blasts. In 163 DS neonates with blasts <10% screened by NGS, 33(20.2%) had small GATA1 clones (Silent TAM); their clinical and haematological features were indistinguishable from 130/163 without mutations. 4 neonates with TAM received low-dose chemotherapy and 1 died. ML-DS has developed in 4/39 TAM, 1/33 Silent TAM and no DS neonates without GATA1 mutations (median follow-up 57 months, range 18- >60). Conclusion: In neonates with DS, acquired mutations in the GATA1 gene are common, often clinically and haematologically silent and confer a risk of ML-DS in TAM and Silent TAM.